OPPORTUNITIES FOR CONTINUOUS EDUCATIONAL SPACE - T. Yu. Krotenko (Вестник университета)
The space of modern education is voluminous. It is so capacious that it can accommodate any number of different educational systems. On the one hand, these are systems of pre-school, General, and vocational education, which in turn include subsystems of the basic level (primary, secondary, and higher professional education, etc.). On the other hand, and this point is discussed in the article, the concept of “educational space” covers not only the system parameters of the largest integrated education system in the scale of society (city, region, country, world), but also other characteristics that make it possible, based on the analysis of their state, structure and dynamics, to speak convincingly about the directions and quality of development of socio-cultural relations in General.